Perbandingan Penggunaan Media Manipulatif dan Media Software Wingeom Terhadap Kemampuan Berpikir Matematis Siswa Sekolah Dasar - Ema Tryana Sari; Dalifa (JURIDIKDAS, 2023)
This study aims to determine the differences of mathematical thinking skills between students who use wingeom software media and manipulative media in the fifth grade elementary school mathematics learning in the XIV group of Bengkulu City. This research is quantitative research. The research method used was a quasi-experimental design with pretest-posttest comparation group design. The population in this study were all fifth grade elementary school students in group XIV of Bengkulu City. The sample is a fifth grade student of SDN gugus XIV Bengkulu City, which is a state school. The sampling technique uses purposive random sampling. The drawing results obtained by the sample were students of VC class SDN 42 Bengkulu City, amounting to 23 students into the experimental class I and class VA SDN 45 Bengkulu City, amounting to 25 students into the experimental class II. The research instrument used a test in the form of a description question that given through pretest and posttest. The data analysis technique in this study is quantitative analysis using descriptive statistics and inferential statistics, namely the t-test. Data from the research results processed using the t-test by looking at the gain values ​​obtained, by the value of tcount of 2.25 and the value of ttable of 2.01. Statistically, there are tcount (2.25)> ttable (2.01) at a significant level of 5%, it can be concluded that there are differences of mathematical thinking skills between students using manipulative media and wingeom software media in mathematics learning in class V SD XIV group of Bengkulu City.